The use of platelet-rich fibrin in combination therapy of mandibular delayed union - Idashkina, N. (Actual Dentistry, 2018)
Purpose: to evaluate the effectiveness of the using injectable platelet-rich fibrin techniques in the prevention and treatment of delayed consolidation of fragments in patients with mandibular fractures. Methods. For the period from 2010 to 2016, 60 patients with a mobility of fragments in the fracture zone in one month after repositioning and fixing the fragments were observed treatment. All patients were randomized into two groups of 30 people, identical in age and sex. The injection of platelet-enriched fibrin (PRF) sub-periosteal along the line of mandibular fracture was performed in addition to the treatment complex for stimulation of reparative osteogenesis by the patients in the second group,. The control group consisted of 19 practically healthy volunteers with absents of clinical signs of acute or chronic diseases, as well as pathology of teeth and periodontal disease. Carried out the extended immunological and biochemical researches, directed on determination of factors which result in disorders of reparative osteogenesis. Results. The use of the pathogenetically determined strategy of prevention and treatment of delayed consolidation of mandibular fractures allowed to achieve in all patients the relief of clinical symptoms of consolidation complications in a short time (up to 7 days). However, clinically reparative osteogenesis in patients in the second group proceeded with some differences: with the formation of significant bone callus in the majority of the first group (in 22 patients (73.3 %), whereas in the group of patients receiving PRF, a pronounced periosteal reaction was noted only in 11 patients (36.7 %). In the second group, a reparative reaction was more often observed in terms of the type of primary delayed contact arrest. Prognostic criteria for the emergence and success of inflammatory complications treatment of mandibular fractures in practically healthy people have been determined. Conclusions. The main factors contributing to the development of delayed consolidation of mandibular fragments are disorders of bone metabolism, processes of free radical lipid oxidation, changes in the functioning of the main cytokines and a decrease in local humoral immunity. The basic program for the treatment of patients with delayed consolidation of the mandibular fractures should include optimization of osteogenesis processes with osteotropic drugs, elimination of the increase in free radical lipid oxidation by antioxidants, and correction of the synthesis of cytokines and immunoglobulins by immunomodulators. Inclusion in the comprehensive prevention and treatment of delayed consolidation of mandibular fractures of the PRF significantly affects the quality of the regenerate. The main laboratory criteria for the effectiveness of complex treatment of delayed consolidation of mandible fragments are the positive dynamics of the parameters of the antioxidant system (SOD and catalase) and the parameters of IL-1β and sIgA. Key words: fracture of lower jaw, delayed consolidation, pathogenesis, reparative osteogenesis, enriched platelets fibrin.